2008
DOI: 10.1007/s00405-008-0734-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep neck infections: a retrospective review of 112 cases

Abstract: The purpose of this study was to review our recent experience with deep neck infections and compare it to the experiences in the available literature. A total number of 112 charts of patients treated for deep neck infections at the department of otolaryngology of our hospital between August 1996 and September 2007 were retrospectively reviewed. All the relevant clinical charts including presentation, origin and site of deep neck infection, radiological, and bacteriological studies and interventions along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
80
6
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 12 publications
20
80
6
10
Order By: Relevance
“…Of the 58 patients with DNI, only in two patients (3 %) was DNI the first manifestation of malignant tumour. Similar results for DNI origin have been observed by other authors (Ridder et al, 2005;Eftekharian et al, 2009;Bakir et al, 2012). The incidence of head and neck cancer initially manifested as DNI was found to be increased in patients aged over 40 years (Lin et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Of the 58 patients with DNI, only in two patients (3 %) was DNI the first manifestation of malignant tumour. Similar results for DNI origin have been observed by other authors (Ridder et al, 2005;Eftekharian et al, 2009;Bakir et al, 2012). The incidence of head and neck cancer initially manifested as DNI was found to be increased in patients aged over 40 years (Lin et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…The same was observed in the study of Zamiri which reported 61.8% and 38.2% patients were from urban and rural areas, respectively. These results show a higher percentage of hospital admissions for the urban citizens despite fewer admissions of rural patients which is probably due to difficulties of access to care or transportation issues, and lower settlements in rural areas (18). The most frequent site of DNSI in our study was submandibular space (50%), followed by parapharyngeal space (25%), peritonsillar (12.3%) and Ludwig's angina (5.4%).…”
Section: Discussionmentioning
confidence: 48%
“…In a study by Bottin 42% of DNSI cases were odontogenic in origin (17). In a retrospective study by Zamiri, odontogenic infection was declared as the most common cause of DNSI (34.3%) (18). Kataria also reported similar results to Zamiri with 34.21% of DNSI due to odontogenic origin (11).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[9][10][11][12][13] The lower second and third molar was most common source of infection in our study. 11% of the patients were found to have osteoradionecrosis of the mandible after a course of radiotherapy for oral cancer.…”
Section: Etiologymentioning
confidence: 51%